Analisis Pengaruh Slot Terhadap Efisiensi Generator Permanent Magnet Synchronous Generators (PMSG) 12 Slot 16 Pole dan 24 Slot 16 Pole Menggunakan FEM (Finite Element Method) - Andika, Rizki; Aini, Zulfatri (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Permanent magnet synchronous generator (PMSG) is a self-excitation generator using a permanent magnet. PMSG has different slot variations so that it has different efficiencies. This study aims to see the effect of slots on the efficiency of PMSG 12 Slot 16 Pole and PMSG 24 Slot 16 Pole. The research method used is to simulate PMSG 12 Slot 16 Pole and PMSG 24 Slot 16 Pole in Finite Element Method (FEM) based software. In the simulation at a rotating speed of 1000 Rpm with a variable in the form of resistance R = 50 Ω PMSG 12 Slot 16 Pole obtained an output value of 1245.29 Watt with an efficiency of 76% while PMSG 24 Slot 16 Pole obtained an output value of 3919 Watt with an efficiency of 86%.Keywords - Permanent Magnet Synchronous generator (PMSG), Slot, Efficiency.